Upper Cervical Spine Stability: Maximum Rotation and the Rotation Stress Test in Clinics - Lorente, Ana I; Maza Frechín, Mario; Pérez Bellmunt, Albert; Hidalgo García, César (Jornada de Jóvenes Investigadores del I3A, 2019)
The rotation stress test is used to evaluate stability of the craniocervical junction by assuming that it gives the maximum rotation. However, a more complex manipulation might show a higher rotation: the rotation with extension and contralateral bending. This was tested in vitro with ten upper cervical spine specimens.